2016
DOI: 10.1016/j.ymeth.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing FUCCI reporters to understand pluripotent stem cell biology

Abstract: The fluorescence ubiquitination cell cycle indicator (FUCCI) system provides a powerful method to evaluate cell cycle mechanisms associated with stem cell self-renewal and cell fate specification. By integrating the FUCCI system into human pluripotent stem cells (hPSCs) it is possible to isolate homogeneous fractions of viable cells representative of all cell cycle phases. This method avoids problems associated with traditional tools used for cell cycle analysis such as synchronizing drugs, elutriation and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…After puromycin selection for about 2 weeks, we isolated two Clover fluorescent protein‐expressing single cell‐derived hPSC clones and confirmed transgene presence by PCR genotyping (Figure 1b). The dominant expression of Clover indicated that the hPSCs are primarily at the S/G 2 phase (Figure 1c,d), which is consistent with a previous report (Singh, Trost, Boward, & Dalton, 2016). Importantly, the engineered hPSCs retained strong expression of pluripotency markers, stage‐specific embryonic antigen‐4 (SSEA‐4; Figure 1e) and octamer‐binding transcription factor 4 (OCT‐4; Figure 1f).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After puromycin selection for about 2 weeks, we isolated two Clover fluorescent protein‐expressing single cell‐derived hPSC clones and confirmed transgene presence by PCR genotyping (Figure 1b). The dominant expression of Clover indicated that the hPSCs are primarily at the S/G 2 phase (Figure 1c,d), which is consistent with a previous report (Singh, Trost, Boward, & Dalton, 2016). Importantly, the engineered hPSCs retained strong expression of pluripotency markers, stage‐specific embryonic antigen‐4 (SSEA‐4; Figure 1e) and octamer‐binding transcription factor 4 (OCT‐4; Figure 1f).…”
Section: Resultssupporting
confidence: 92%
“…Due to the importance of cell‐cycle regulation for both the self‐renewal and differentiation of hPSCs, a stable and robust cell‐cycle visualization system could effectively provide more valuable information to broaden the applications of hPSCs. Although the FUCCI system has been widely used in many dynamic models, including zebrafish (Choi et al, 2013), mouse (Abe et al, 2013), and stem cells (Calder et al, 2013; Coronado et al, 2013; Jovic et al, 2013; Roccio et al, 2013; Singh et al, 2013; Singh et al, 2016), a lineage‐specific hPSC‐FUCCI reporter has not yet been generated for versatile and high‐throughput analysis of cell‐cycle behavior during hPSC self‐renewal and differentiation. Here, we have established and validated a robust and universally applicable FUCCI system in hPSCs for continuous and lineage‐specific reporting of cell‐cycle behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Whether expression of RB or Cdkn is activated first, or both are activated together is not known. The recent development of improved methods to sort cells into discrete phases of the cell cycle (Pauklin and Vallier, 2013 ; Singh et al, 2016 ), will aid in resolving this issue.…”
Section: The Truncated Mes Cell Cyclementioning
confidence: 99%
“…By far the most useful recent technology developed to study the cell cycle is the Fluorescent Ubiquitination-based Cell-Cycle Indicator (FUCCI) system (Sakaue-Sawano et al, 2008 ). This sensor allows for live tracking and clear demarcation of cells in the G1and S/G2/M phase of the cell cycle and when combined with FACS, these subsets of cells can be further subdivided into Early G1, Late G1, S, and G2/M (Pauklin and Vallier, 2013 ; Singh et al, 2016 ). FUCCI has revolutionized how we study the cell cycle by creating a non-disruptive, near native system to study any cell cycle related phenomena.…”
Section: Dissecting the Es Cell Cycle: A Changing Paradigm Requiring mentioning
confidence: 99%
“…[3335] WA09 hESCs were grown in media containing HEREGULIN β1 (10 ng/ml; Peprotech), ACTIVIN A (10 ng/ml; R&D Systems), and human LONGR3 insulin-like growth factor 1 (IGF-1; 200 ng/ml; Sigma) and harvested at confluency. [3637] The U937 (ATCC® CRL-1593.2™) and U1 (NIH AIDS Reagent Program #165) pleural effusion, lymphocyte cell line was grown in a humidified incubator at 37ºC and 5% CO2. Cells were grown in RPMI1640 supplemented with 10% fetal bovine serum and 30 ng/mL Gentamicin.…”
Section: Methodsmentioning
confidence: 99%